Analysis of reinforced concrete deep beam strengthened by CFRP strips using ANSYS program - Faraj, Sara Saad; Hamad, Dr. Nagham Tariq; Hammoodi, Ahmed Hasan; Abduljalel, Dr. Ban Sahib (International Journal of Engineering and Technology, 2018)
This paper presents the results of finite element analysis of strengthened reinforced concrete deep beams using the software package ANSYS 12.The work includes modeling seven reinforced concrete deep beams, same configuration have been considered with different strengthen-ing schemes. In order to find out the best strengthening mechanisms, the main variables considered in this work include the effect of fiber orientation (90° or 45° CFRP strips with respect to beam longitudinal axis), the effect of using longitudinal CFRP strips with transverse CFRP strips (90° or 45° CFRP strips) and effect of anchoring the transverse CFRP strips (90° or 45° CFRP strips).The analytical results were discussed based on shear resistance, mid span deflection. The results reveal that externally CFRP strips can significantly increase the ultimate shear resistance and increase the stiffness of the deep beams.